The examination of the relationship between stigma and self-efficacy in women undergoing infertility treatment - Yeter Durgun Ozan; Ugur Deger; Sumbul Di̇ncer (Medicine Science)
This research aimed to explore the connection between stigma and self-efficacy in women undergoing infertility treatment. The research was designed as a descriptive and correlational study. The study's sample included 264 infertile women undergoing treatment for infertility. Data collection was conducted using the ‘personal information form', the ‘infertility self-efficacy scale,' and the ‘infertility stigma scale'. Based on the findings, women's mean score on the Infertility Stigma Scale was 55.0 ± 24.4. The highest mean sub-dimension score was obtained from the public stigma, one of the sub-dimensions of the infertility stigma scale (18.9 ± 4.8). A notable negative correlation was found between the scores of the infertility stigma scale and the infertility self-efficacy scale (r=-0.28, p [Med-Science 2024; 13(4.000): 984-9]